Enhancing the low-velocity impact resistance of ultra-high performance concrete by an optimized layered-structure concept. (1st November 2020) - Cao, Y.Y.Y.; Liu, G.; Brouwers, H.J.H.; Yu, Qingliang
Abstract: Low-velocity impacts are common in the civil engineering field. Ultra-High Performance Fiber Reinforced Concrete (UHPFRC) is a promising material to resist these impacts. When a UHPFRC beam is under low-velocity impacts, the damage in its distant region caused by the reflected tensile waves is far more serious than that in the impacted region caused by compression. This damage distribution and the more significant effects of steel fibers on the tensile properties of UHPFRC inspire the concept of applying a layered structure with different fiber amounts at different regions of the beam. This study investigates the dynamic resistance of layered UHPFRC under repeated low-velocity drop-weight impacts. The results show that the double-layered UHPFRC achieves a superior resistant capacity compared to its single-layered counterpart, e.g. an approximate 28% enhancement of the absorbed impact energy is obtained by the double-layered beam U0.6 h –1.6 h than that of the corresponding single-layered UHPFRC with an identical fiber amount. Further, a new model to estimate the absorbed energy of the layered UHPFRC under multiple drop-weight impacts is developed and validated using the experimental results. By separating the contributions of the matrix and the fiber, the model confirms the important effects of the steel fibers on the beam absorbed impact energy, as well as the improved fiber utilization efficiency of the double-layered beam. This study contributes to improving the dynamic performance of UHPFRC under low-velocity impacts, and promotes the potential utilization of layered UHPFRC composite in civil engineering.